Ovulation synchronization with progestins prior to a Cosynch protocol in beef cows - M.A. Medina-Britos; A.M. Richardson; G.C. Lamb; B.A. Hensley; T.J. Marple; Jeffrey S. Stevenson; Sandra K. Johnson (Kansas Agricultural Experiment Station Research Reports, 2001)
A multi-location study was conducted using suckled beef cows in Minnesota and Kansas to test the benefit of adding a source of progestin to the Cosynch ovulation synchronization protocol (injections of GnRH, 7 days before and 48 hr after an injection of PGF2", with a fixed-time artificial insemination (AI) administered at the same time as the second GnRH injection). Feeding melengestrol acetate (MGA) for 14 days followed in 12 days by the Cosynch protocol was compared to the Cosynch protocol with the addition of a progesterone-impregnated insert (CIDR) placed in the vagina for 7 days concurrent with the first GnRH injection. Pregnancy rates after the first AI (timed AI) were 22% greater with the CIDR insert, whereas conception rates for those cows returning to estrus were greater for cows previously fed MGA. Total pregnant cows after two inseminations were 64% for CIDR cows and 59% for MGA cows.
Keywords: Cattlemen& #x27; s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Ovulation synchronization; Cows; Embryo survival; MGA; CIDR